ANALISIS KESESUAIAN LAHAN TAMBAK BERDASARKAN PARAMETER FISIS & CHEMIS UNTUK BUDIDAYA KEPITING BAKAU (Scylla spp) DI KELURAHAN DEGAYU KOTA PEKALONGAN - Hisyam Abdurrahman Risa; Hadi Pranggono; Tri Yusufi Mardiana (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah (Bappeda) Kota Pekalongan, 2019)
This study is to determine the level of land suitability as well as assessing the extent to which the potential of land resources can be utilized for the cultivation of mangrove crabs. The purpose of this research is to know the level of land suitability based on physical and chemical parameters for the cultivation of mangrove crab in the pond area in Degayu Village. This research was conducted on 4 until 9 June 2018 at 4 ponds in Degayu Village. Water parameters measured are temperature, salinity, water pH, DO, ammonia, nitrate, phosphate, soil texture, soil pH. The feasibility analysis of pond land is done by using Scoring Method with 3 values of feasibility class interval that is very suitable (S1), according (S2), not appropriate (S3). The result from 4 point of pond station representing Degayu Subdistrict showed temperature value ranged from 31-34 ºC, salinity ranged between 18-28 ppt, water pH ranged from 6,3-7,9 ppm, DO ranged from 3.0-6,0 ppm, ammonia ranged from 0.1-0.3 mg/l, nitrate ranged from 1.4 to 1.8 mg / l, phosphate ranged from 1 -2 mg / l, soil texture was generally dominated by a mixture of clay / clay, sand, and dust and soil pH ranges from 7.0 -7.5. At station 1,3 gets S1 value (very suitable) while station 2,4a, and 4b got S2 value (accordingly). Pond in Degayu village has a category of appropriate feasibility class (S1) to support the activities of mangrove crab cultivation. Keywords: Crab, Land suitability, Water quality and soil parameters